The Effect Of Quercetin And Dihydroquercetin On The Activity Of The Sucrase Enzyme In The Small Intestine In Case Of Experimental Hypothyroidism (Journal of Pharmaceutical Negative Results, 2022)
The development of new drugs for the treatment of hypothyroidism is one of the crucial problem of medicine, physiology andpharmacology. The hypoglycemic properties of biological active compounds were studied in this research to determine the effect ofthyroid hormones on the functional parameters of the small intestine in case of experimental hypothyroidism and the correctionmechanism with natural substances. In the study, the effect of quercetin and dihydroquercetin polyphenols on the activity of smallintestine hydrocarbons in a healthy body was studied and the mechanism of correction with these substances after hypothyroidismwas studied.